(untitled) (Global Journal of Science Frontier Research, 2022)
This study evaluated the use of information and communication technologies (ICTs) among arable farmers in Ekiti State, Nigeria. A multi-stage sampling procedure was employed for the selection of 240 respondents in the study area. Collection of primary data from the respondents was through a wellstructure interview schedule. Descriptive and inferential statistics were used to analyse data. The result of the findings revealed that more than one-third of the respondents(66.7%) were male. The mean age of the respondents was 47years and had a mean household size of 5 persons. Mostly (95.8%) had formal of education and a mean farming experience of 23 years. Farmers were aware of mobile phone (3.75), radio (3.59), television (3.41), internet (2.59) and video recorder (2.57).The mostly used ICTs tools by the respondents were mobile telephone (3.77), radio (3.57) and television (3.33).Farming experience, household size and level of awareness on ICTs had significant influence on level of usage of ICTs among arable farmers. Limited finance, high cost of ICTs facilities, unstable power supply, limited technical knowhow, language illiteracy, inadequate infrastructure and inadequate access to agricultural information were major constraints to the use of ICTs by the farmers. Government should therefore create more awareness to sensitize, provide adequate training on the use of ICTs and incentives to enhance ICTs usage by these farmers for better productivity.